2011
DOI: 10.3892/ijo.2011.1254
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic gemcitabine resistance in a novel pancreatic cancer cell line is associated with cancer stem cell-like phenotype

Abstract: Abstract. Pancreatic ductal adenocarcinoma (PDA) remains one of the most lethal malignancies in the world, often diagnosed at an advanced stage, resistant to conventional chemotherapy and having high invasive and metastatic potential. The mechanism of drug resistance of PDA is still not clear. In the present study, we established two novel pancreatic cancer cell lines PAXC-002 and PAXC-003 from human primary xenograft models. The cell lines were characterized by morphology, karyotype, pancreatic cancer marker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 35 publications
0
13
1
Order By: Relevance
“…Whether these markers are the most suitable ones for identification of CSCs is not under investigation here, as it would require more than one primary PDAC cell line in a larger study. We found that expression of CD133+, the triplet CD44+/CD24+/ESA+, and activity of ALDH1 in JoPaca-1 at passage 10 were much higher than reported in other cell lines, with 61%, 46%, and 28% respectively [54], [56], [57]. Even the overlap of two independent markers accounts for a substantial percentage of the whole JoPaca-1 population.…”
Section: Discussioncontrasting
confidence: 54%
“…Whether these markers are the most suitable ones for identification of CSCs is not under investigation here, as it would require more than one primary PDAC cell line in a larger study. We found that expression of CD133+, the triplet CD44+/CD24+/ESA+, and activity of ALDH1 in JoPaca-1 at passage 10 were much higher than reported in other cell lines, with 61%, 46%, and 28% respectively [54], [56], [57]. Even the overlap of two independent markers accounts for a substantial percentage of the whole JoPaca-1 population.…”
Section: Discussioncontrasting
confidence: 54%
“…There is an increasing body of evidence that Cancer Stem Cells (CSC) are largely involved in the drug resistance in cancer (35). We hypothesized that treatment with orlistat decreases the stemness of PANC-1 cells to promote gemcitabine sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…When treatment was ceased, tumor outgrowth was resumed and CSC marker expression returned to pre-treatment levels [260]. Treatment with gemcitabine also increased the proportion of CD133 + cells in the tumor cell population both in vitro and in vivo , and cells positive for CD133 showed strong resistance to gemcitabine induced apoptosis [154,191,261]. …”
Section: Pancreatic Cancer Stem Cells and Emtmentioning
confidence: 99%